2005
DOI: 10.1088/0741-3335/47/10/001
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of particle transport in the scrape-off layer plasmas of Alcator C-Mod and DIII-D

Abstract: Scrapeoff Layer (SOL) data from DIII-D and C-Mod have been acquired and analyzed for radial particle transport based on a particle balance model. This has allowed a detailed comparison for L-mode plasmas. The inferred radial particle flux, Γ ⊥ (r), is parameterized in terms of diffusive [D eff (r) ≡ Γ ⊥ (r)/∇n(r)]and convective particle transport [v eff (r) ≡ Γ ⊥ (r)/n(r)]. The magnitude of the inferred D eff or v eff increases across the SOL for both tokamaks. The inferred D eff or v eff in the 'far' SOL (one… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

14
101
2

Year Published

2007
2007
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 67 publications
(117 citation statements)
references
References 39 publications
14
101
2
Order By: Relevance
“…Comparisons between DIII-D and C-Mod yield the same trends [101]. The opacity of the far SOL to neutral penetration may offer part of the explanation for the appearance of a shoulder [101]; if wall-recycled neutrals ionise in the far SOL, they are rapidly transported back to the wall as ions.…”
Section: Particle Transport In the Solmentioning
confidence: 66%
See 1 more Smart Citation
“…Comparisons between DIII-D and C-Mod yield the same trends [101]. The opacity of the far SOL to neutral penetration may offer part of the explanation for the appearance of a shoulder [101]; if wall-recycled neutrals ionise in the far SOL, they are rapidly transported back to the wall as ions.…”
Section: Particle Transport In the Solmentioning
confidence: 66%
“…The abovementioned comparisons between C-Mod, DIII-D, and JET shows SOL profiles (including D eff and v eff ) that are similar in shape and magnitude when scaled according to dimensionless plasma physics parameters [100,101]. In particular, v eff is found to have a weak dependence on those dimensionless parameters.…”
Section: Particle Transport In the Solmentioning
confidence: 99%
“…Several experiments have shown evidence of density profile flattening at high Greenwald fraction, f G n=n G , or low plasma current I p . These include C-Mod, 27,28,264 DIII-D 24,264 and TCV. 52,93 In each case, the density profile becomes increasingly flat, and the density at the wall increases, as a function of f G or 1/I p .…”
Section: Experimental Evidence For Collisionality Dependencementioning
confidence: 99%
“…Ref. 264 describes a series of dimensionless scaling experiments on C-Mod and DIII-D showing that the SOL transport is very similar in the two machines. When profiles of v eff ðxÞ were plotted for collisionalities spanning an order of magnitude on C-Mod, it was found that v eff increased with collisionality near the separatrix, consistent with earlier work, 28,265 but was insensitive to collisionality near the wall.…”
Section: Experimental Evidence For Collisionality Dependencementioning
confidence: 99%
“…This approach was justified by experimental findings in Alcator C-mod [Lipschultz_PPCF05] and DIII-D [Whyte_PPCF05,Rudakov_NF05] that showed significant interaction of the plasma with the main chamber walls occurs in high plasma density operations. In these experiments, the 13 CH 4…”
Section: Introductionmentioning
confidence: 99%